Analisis Bauran Komunikasi Pemasaran dalam Meningkatkan Penjualan pada Thrifting ArfaStore Kotabumi Lampung - Rahmania Rahmania; Hagi Julio Salas (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the implementation of the marketing communication mix carried out by ArfaStore in Kotabumi, Lampung, in an effort to increase sales and strengthen customer relationships sustainably through creative, innovative, and customer satisfaction-oriented communication strategies. The research uses a qualitative approach with a descriptive method to gain an in-depth understanding of marketing communication strategies that include elements of advertising, sales promotion, public relations, direct marketing, digital marketing, and personal selling. The data were obtained through in-depth interviews, direct observations, and documentation, then analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results show that ArfaStore has successfully integrated various elements of marketing communication effectively, such as utilizing social media for promotion, offering attractive discounts, and building good relationships with customers. These efforts have proven to increase sales and consumer loyalty. This study recommends that thrifting business owners further maximize the role of social media and adapt their communication strategies to the dynamic and competitive market needs.